U.S. Dollar Currency Premium in Corporate Bonds - Caramichael, John (IMF Working Papers; Working Paper ;, 2021)
We isolate a U.S. dollar currency premium by comparing corporate bonds issued in the dollar and the euro by firms o utside t he U .S. a nd e uro a rea. We make s everal empirical observations that dissect the perceived advantage of borrowing in the dollar. First, while the dollar dominates global debt issuance, borrowing costs in the dollar are more expensive without a currency hedge and about the same with a currency hedge when compared to the euro. This observed parity in currency-hedged corporate borrowing stands in contrast to the persistent deviation from covered interest parity in risk-free rates. Second, we observe a dollar safety premium in relative hedged borrowing costs, found in the subset of bonds with high credit ratings and short maturities, attributes similar to those of safe sovereigns. Finally, we find that firms flexibly adjust the currency mix of their debt issuance depending on the relative borrowing cost between dollar and euro debt. In sum, the disproportionate demand for U.S. dollar debt is reflected in higher issuance volumes that drive up the currency hedged dollar borrowing costs such that at the margin they equate to euro borrowing costs.